Youth and the 25th Revolution in Egypt: agents of change and its multiple meanings - El Sharnouby, Dina (AUC Knowledge Fountain, 2012)
The 25th of January 2011 marks an important date for Egypt and the world. Not only did former President Hosni Mubarak who has ruled Egypt for 30 years step down, but the youth who were once conceived as incapable of change were hailed as those who brought about this transformation. Yet how could the youth organize and bring about such a change that was not only unthinkable for many, but not one who took to the streets on the 25th imagined they could topple Hosni Mubarak in 18 short days. In this thesis I thus ask: 1) how have youth been deployed before and after the 25th of January Revolution as agents of change, 2) what kind of transformations are youth imagining for Egypt. Several events since the 1990s contributed to sharpening the youth consciousness culminating in taking the streets on January, 25th demanding ÃƒÂ¢ change, freedom, and social justice. I argue that, especially since the 1990s, a series of events and protests contributed to the formation of this generational consciousness which materialized on January 25th when thousands of mainly youth went on the streets to demand change. During the 1990s the adoption of neoliberal strategies pushed the state to minimize its role and promote civil society activities many of which focused on development. Many members of the organization were mainly focused on helping the poor (as a religious responsibility) without demanding social justice on challenging their own privileges. Secondly, a number of protests in the 2000 onwards were ushered by different protest movements such as Kefaya and the 6th of April youth movement. As national strategies failed to employ the majority of the youth, they became a burden on society. Not being able to afford a good education, employment, or marriage, Egyptian youth transformed from being the hope of the country in the 1950's to a serious social problem n the by the 1980's (Ibrahim, 2008). This affected youth's everyday interactions as they were financially dependent on their families, while their leisure time activities were seen as dangerous or morally corrupt potentially leading to criminal activities, drug abuse, and immorality. To channel particular categories of youth, NGOs offered the path of civic participation as a means to harness their energies toward development, while maintaining structurally the status quo of society, economy and polity. By taking the streets on January the 25th, Egyptian youth for a short period transformed from being the problem to being the hope of the country. Through the governance of Tahrir square, Egyptian youth proved their eagerness to change and with the ousting of Mubarak they were celebrated as heroes. Tahrir Square thus played a major role in reviving the youth and in transforming them from the problem to the hope of the country. Class, gender, and religion shaped the imagery of which young person can bring about change. A masculine, upper middle class man was mainly attached to the new young person that can change Egypt. However, now, a clash of generations is clearly taking place in which the emerging youth generation fights for political inclusion. Different events such as the protests on Mohamed Mahmoud Street (just off of Tahrir Square) and in front of the cabinet, or the parliamentary elections, are just some examples of power negotiations between the "old" and "new" generations. By developing a generational consciousness, there is hope that youth can bring about change, however, depending on their age, class, religion, and gender, their experiences differ giving them different outlooks on the future and also a potential source of division among this generation. My research project focused on youth who both demonstrated and protested during the Revolution and those who did not. In addition, I analyzed the national Al Ahram newspaper in the years 2000, 2004, 2008, 2010, and 2011and attended many public talks in order to unveil how youth were conceived as the problem before the Revolution and transformed into the hope of the country during the 18 days of the uprising. With a new generational consciousness, many young people are hopeful for a better future, however, their inexperience in politics makes it a difficult task to achieve.